2008
DOI: 10.1007/s00405-008-0786-6
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate interslice gap for screening coronal paranasal sinus tomography for mucosal thickening

Abstract: The objective of this study was to establish the appropriate interslice gap for screening coronal paranasal sinus tomography to identify sinus mucosal thickening. We reviewed 100 coronal paranasal sinus tomographic scans (interslice gap, 2 mm) that had been performed at our institution between January 2004 and November 2004 to evaluate rhinosinusitis. Digital photographs of all slices from each tomographic scan were taken. The intervening slices were eliminated to form six different sets of interslice gaps of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 29 publications
1
45
0
1
Order By: Relevance
“…In a study analyzing sinus biopsies (6) or magnetic resonance imaging (16). The mucosa could be seen only at a thickness of 2 mm or above, and, therefore, historically, 2 mm was considered a reliable threshold for pathological mucosal swelling (9). For both groups analyzed in the present study, the differences between the measured mucosal values were not statistically significantly different when comparing the sagittal and coronal slices within the same group, but the values for the group with apical pathologies were statistically significantly higher when compared with patients without apical lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study analyzing sinus biopsies (6) or magnetic resonance imaging (16). The mucosa could be seen only at a thickness of 2 mm or above, and, therefore, historically, 2 mm was considered a reliable threshold for pathological mucosal swelling (9). For both groups analyzed in the present study, the differences between the measured mucosal values were not statistically significantly different when comparing the sagittal and coronal slices within the same group, but the values for the group with apical pathologies were statistically significantly higher when compared with patients without apical lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In CT and magnetic resonance imaging studies, coronal slices are well established for evaluating the mucosal thickness in the maxillary sinus, and the measurements are always performed perpendicularly to the underlying bone (5)(6)(7)(8)(9). The available literature describing potential local or systemic influences on the thickness of the Schneiderian membrane identifies many different factors.…”
mentioning
confidence: 99%
“…Similarly, Pazera et al [24] reported a prevalence of 23.7% and Janner et al [20] reported 37% of cases with membrane thickening. In a recent study, Brüllmann et al [17] found 74% of evaluated sinuses had sinus findings upon CBCT examination. These differences in prevalence might result from the different inclusion criteria among the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Mucosal thickening >2 mm is considered a threshold for pathological thickness [17]. Although mucosal thickening is the most common radiographic finding observed regarding sinus pathology [18], the knowledge regarding its clinical significance on the outcomes of dental implants and grafting in the maxillary sinuses is still limited [19].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested that, on average, the normal thickness of healthy sinuses can be approximately 1 mm, with considerable variation among individuals [14]. In general, 2 mm was considered a reliable threshold for pathological mucosal swelling [15]. In our study, mucosal thickness over 2 mm was accepted as pathologic.…”
Section: Discussionmentioning
confidence: 61%